PULL STRATEGY: A MARKETING STRATEGY PUBLIC RELATIONS TO MAINTAIN CUSTOMER LOYALTY - angel purwanti (Jurnal Apresiasi Ekonomi, 2018)
Customer loyalty is most important asset for every company. Customer loyalty gives company many benefits such as repeat purchase and recommendation to third party. This makes many companies always try figure out the ways to maintain customer loyalty. This research is held in PT. Zinkpower Batam Indo in Jl. Brigjend Katamso KM 6,2 Tanjung Uncang, Batam. This company is pioneer of galvanizing plant in Batam and proven to have high quality of galvanizing. PT. Zinkpower Batam Indo is subsidiary of Kopf Group, a mother company with the same field. This research aims to determine PT. Zinkpower Batam Indo Marketing Public Relations’s strategy to maintain their customer loyalty. The method used is descriptive qualitative approach. Data collection technique in this research using depth interview, participant observation & documentation. The result is Marketing Public Relations using pull strategy to main customer loyalty, such as customer satisfaction survey, complain handling, discount and one stop service. Implementation of pull strategy proved can maintain the loyalty that will explained in this research. Keywords: Marketing Public Relations, Pull Strategy, Loyalty